Proposed new interior design of restaurant for D’Paya Serai Restaurant at Lot 3 & 5 Jalan Plumbum S 7/S, Seksyen 7, 40000 Shah Alam, Selangor Darul Ehsan / Nor Haizum Mohd Harapi - Mohd Harapi, Nor Haizum (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design for D’Paya Serai Restaurant at lot 3 & 5, Jalan Plumbum S 7/s, Seksyen 7, 4000 Shah Alam, Selangor. This proposed restaurant is to attract customers, mostly on student and family to try the great Kelantan food. With the outcome of a new D’Paya Serai Restaurant, it is hoped to make this restaurant more recognizable and assist more customers. The concept and image is also applied to both interior and exterior to appeal the restaurant will be able to lure more customers. There were several researches done to succeed this restaurant final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the D’Paya Serai Restaurant image in terms of function and aesthetic value.